APPLYING MONETARY REGULATION TO CURRENT TRENDS IN SMALL OPEN ECONOMIES - Yevhen Bublyk (Izdevnieciba "Baltija Publishing", 2021)
Significant changes in approaches to the monetary regulation of economic stabilization and growth are currently being completed. The processes of change that began under the influence of the global financial crisis have now become inevitable. Determining the main directions of these changes and the possible consequences for small open economies is one of the most important tasks of scientific research. Timely adaptation of national monetary systems in the initial stages of transformation can enable countries to overcome the consequences of the pandemic and make up for lost time. The article analyzes a number of the most characteristic changes in practice and theoretical views on monetary policy. Among them is the change in views on the role and purpose of inflation targeting under the influence of many years of massive emission practices. The identified synchronism of inflation for developed and developing countries gives reason to expect attempts at quantitative easing on the part of developing countries. While they may be postponed due to the acceleration of producer price growth. The tendency to revise the fiscal component in the dualism of fiscal policy to strengthen the targeting of emission is substantiated. The low efficiency of measures of monetary easing and stimulation through the credit channel is noted. The limited impact on the growth of aggregate demand with an increase in the debt burden should lead to a revision of the existing practice of emission and reduction of interest rates. One of the important drivers of changes in monetary regulation is the process of digitalization. Despite certain risks of deficiencies in the effectiveness of central bank monetary policy, the spread of shadow banking, digital currencies and direct lending operations, digitalization is creating new opportunities for financial control and audit. On the basis of the analyzed trends, a conclusion was made about the current tasks of modernization of monetary policy in countries with small open economies, including Ukraine.